CONCENTRATIONS OF Cr, Cu AND Zn IN THE SHELL HARD CLAM (Meretrix meretrix) FROM THE COASTAL WATERS SEI NAGALAWAN SERDANG BEDAGAI REGENCY NORTH SUMATRA PROVINCE - Simanjuntak, Benny Ly; Amin, Bintal; Nedi, Syahril (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTThis research was conducted on February 2018 by taking samples of M.meretrix  clams in the coastal waters of Sei Nagalawan, Serdang Bedagai Regency in North Sumatra Province. This research aims to know the metals Cr, Cu and Zn concentration in different sizes hards clams M. meretrix with different sizes and  the difference in metal concentration between the stations. This research also aims to know the Metal Pollution Index (MPI) in coastal waters of Sei Nagalawan Village. Cr was highest in 19,5293 µg/g) of the stations is 3. Cu was highest in 4,4187µg/g) of the stations is 3. Zn was highest in 47,8307µg/g) of the larger stations is 3. The value of the index metal pollution (MPI) Coastal Waters of Sei Nagalawan Village is 11,56 is classified in the category of high. Key Words : Heavy Metals, Pollution, North Sumatra, Meretrix meretrix